PENGARUH PIJATAN SLOW STROKE BACK MESSAGE (SSBM) TERHADAP PENURUNAN NYERI FASE AKTIF KALA SATU PERSALINAN IBU PRIMIGRAVIDA - NOVITA BR GINTING MUNTHE (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2020)
One of the needs of mothers in labor is the reduction of pain or pain. Pain reduction techniques during labor consist of pharmacological therapy and nonpharmacological therapy. One of the non-pharmacological methods of reducing labor pain is Slow Stroke Back Massage (SSBM). This study aims to determine the effect of SSBM on the reduction of active phase pain in the first stage of labor of primigravida mothers in Lamsiah Clinic in 2020. Quantitative research methods. This type of research is a quasi-experimental design with nonequivalent control group design. The study population was all primigravida mothers giving birth at the Lamsiah Clinic as many as 30 people. The sample selection uses purposive sampling and the number uses the Lameshow formula as many as 16 people as the intervention group and 16 others as the control group. The results of the study using the T test showed that the intervention group obtained p-value = 0,000. While in the control group, the value of p-value = 0.333 was obtained. The conclusion is that the effect of a SSBM massage on the reduction of pain in the active phase in the first labor of primigravida mothers in the intervention group, but in the control group, no significant effect. It is expected that health workers in the Lamsiah Clinic will provide health education to mothers during ANC on non-pharmacological efforts in the form of a SSBM massage as an effort to reduce labor pain intensity.